Adaptive MR-Guided Stereotactic Radiotherapy is Beneficial for Ablative Treatment of Lung Tumors in High-Risk Locations - Regnery, Sebastian; Buchele, Carolin; Weykamp, Fabian; Pohl, Moritz; Hoegen, Philipp; Eichkorn, Tanja; Held, Thomas; Ristau, Jonas; Rippke, Carolin; König, Laila; Thomas, Michael; Winter, Hauke; et al. (Frontiers in Oncology, 2022)
Purpose: To explore the benefit of adaptive magnetic resonance-guided stereotactic body radiotherapy (MRgSBRT) for treatment of lung tumors in different locations with a focus on ultracentral lung tumors (ULT). Patients & Methods: A prospective cohort of 21 patients with 23 primary and secondary lung tumors was analyzed. Tumors were located peripherally (N = 10), centrally (N = 2) and ultracentrally (N = 11, planning target volume (PTV) overlap with proximal bronchi, esophagus and/or pulmonary artery). All patients received MRgSBRT with gated dose delivery and risk-adapted fractionation. Before each fraction, the baseline plan was recalculated on the anatomy of the day (predicted plan). Plan adaptation was performed in 154/165 fractions (93.3%). Comparison of dose characteristics between predicted and adapted plans employed Bayesian linear multilevel models. Results: Plan adaptation decreased the proportion of fractions with violated planning objectives from 94% (predicted plans) to 17% (adapted plans). In most cases, inadequate PTV coverage was remedied (predicted: 86%, adapted: 13%), corresponding to a moderate increase of PTV coverage (+6.3% [5.3 – 7.4%]) and biologically effective PTV doses (BED10) (BEDmin: +9.0 Gy [6.7 - 11.3 Gy], BEDmean: +1.4 Gy [0.8 – 2.1 Gy]). This benefit was smaller in larger tumors (-0.1 %/10 cm³ PTV [-0.2 – -0.02 %/10 cm³ PTV]) and ULT (-2.0 % [-3.1 – -0.9 %]). Occurrence of exceeded maximum doses inside the PTV (predicted: 21%, adapted: 4%) and violations of OAR constraints (predicted: 12%, adapted: 1%, OR: 0.14 [0.04 – 0.44]) was effectively reduced. OAR constraint violations almost exclusively occurred if the PTV had touched the corresponding OAR in the baseline plan (18/19, 95%). Conclusion: Adaptive MRgSBRT is highly recommendable for ablative treatment of lung tumors whose PTV initially contacts a sensitive OAR, such as ULT. Here, plan adaptation protects the OAR while maintaining best-possible PTV coverage.